Reproducción de Oenomaus ortignus (Lepidoptera: Lycaenidae) en Barva, Heredia, Costa Rica - Renán Calvo (Revista de Biología Tropical, 1998)
A group of Annona cherimolia (Mill:Annonaceae) trees was studied in Barva, Heredia, Costa Rica (June 1991-August 1992) to record egg-laying sites of the butterfly Oenomaus ortignus (Lepidoptera: Lycaenidae). Used fruits often dehydrated and fell before maturity. Eggs are laid in fruits independently of fruit ontologic state and of height above ground. Tree parts less frequently used to lay eggs are flower primordia, leaves and stems, but the larvae move to fruits when food reserves are depleted. Pupation occurs outside the fruit. Pupae emit sound, possible for defence.